Polydatin attenuates tubulointerstitial fibrosis in diabetic kidney disease by inhibiting YAP expression and nuclear translocation - He, Manlin; Feng, Lan; Chen, Yang; Gao, Bin; Du, Yiwei; Zhou, Lu; Li, Fei; Liu, Hongbao (Frontiers in Physiology, 2022)
The activation of Yes-associated protein (YAP) pathway is mutually causal with the increase of extracellular matrix (ECM) stiffness. Polydatin (PD) has been proved to have anti-fibrosis effect in diabetic kidney disease (DKD), but it is still a mystery whether PD participates in YAP-related mechano-transduction. Therefore, this study intends to solve the following two problems: 1) To construct an in vitro system of polyacrylamide hydrogels (PA gels) based on the true stiffness of kidneys in healthy and DKD rats, and observe the effect of PD on pathological matrix stiffness-induced YAP expression in renal fibroblasts; 2) Compared with verteporfin (VP), a pharmacological inhibitor of YAP, to explore whether the therapeutic effect of PD on DKD in vivo model is related to the regulation of YAP. In this study, the in vitro system of PA gels with 3 kPa, 12 kPa and 30 kPa stiffness was constructed and determined for the first time to simulate the kidney stiffness of healthy rats, rats with DKD for 8 weeks and 16 weeks, respectively. Compared with the PA gels with 3 kPa stiffness, the PA gels with 12 kPa and 30 kPa stiffness significantly increased the expression of YAP, α-smooth muscle actin (α-SMA) and collagen I, and the production of reactive oxygen species (ROS) in renal fibroblasts, and the PA gels with 30 kPa stiffness were the highest. PD significantly inhibited the above-mentioned changes of fibroblasts induced by pathological matrix stiffness, suggesting that the inhibition of PD on fibroblast-to-myofibroblast transformation and ECM production was at least partially associated with regulating YAP-related mechano-transduction pathway. Importantly, the inhibitory effect of PD on YAP expression and nuclear translocation in kidneys of DKD rats is similar to that of VP, but PD is superior to VP in reducing urinary protein, blood glucose, blood urea nitrogen and serum creatinine, as well as decreasing the expression of α-SMA and collagen I, ROS overproduction and renal fibrosis. Our results prove for the first time from the biomechanical point of view that PD is a potential therapeutic strategy for delaying the progression of renal fibrosis by inhibiting YAP expression and nuclear translocation.